RF Front-End Design for Software Defined Radio - Maurer, Linus; Weigel, Robert (Wireless World Research Forum, Helsinki, Finland, 2001)
Multimode, multiband transceivers were once seen as desirable but unachievable goal, particularly when considering small, battery-powered terminals. There are, however, significant market-pulls requiring just such a device and dual-mode systems (albeit with largely separate hardware) are now a reality. The next revolution will be the production of so-called flexible architecture terminals, in which the same hardware is used for all modulation formats and bands, with internal software determining the mode to be utilized [1]. The specifications required for each block and the upcoming technological advancements should be examined. Based on this approach, a realistic evaluation of architectures, that can handle the task, should be possible.
elib2cris::1512001600,maurer2001a